Requirements-oriented spectrum sharing for OFDMA cognitive radio networks - Chi ZHANG; Bi-qing ZENG; Jin-song YANG; Xiao-hong XIE (Tongxin xuebao)
Considering the satisfaction of the secondary network communication requirements,a two-stage model was proposed to address the spectrum leasing and allocation problem in OFDMA cognitive radio networks(CRN).At the first stage of the model,the secondary base station(SBS)collected channel capacity requirements of the secondary network,and rent the spectrum resource from multiple primary base stations(PBS).The trade behaviors between the PBS and the SBS were modeled with a Bertrand game,and adopted the Nash equilibrium as the pricing scheme.At the second stage,with the Nash bargaining solution(NBS),the subcarriers and power allocation problem were defined as a nonlinear programming problem,and obtained the solution by Lagrange multiplier method.Comparing with the other spectrum allocation schemes,simulation results show the proposed spectrum sharing scheme can satisfy each secondary user’s communication requirements more fairly and efficiently.